Solvatochromic fluorescent carbon dots as optic noses for sensing volatile organic compounds. Issue 86 (5th September 2016) - Zheng, Min; Li, Yang; Zhang, Yujian; Xie, Zhigang
Abstract : Amphiphilic carbon dots (CDs) with strong solvatochromism were synthesized via solvothermal method. Abstract : Amphiphilic carbon dots (CDs) with strong solvatochromism were synthesized via solvothermal method. The as-synthesized CDs demonstrate outstanding photoluminescence properties consisting of a high fluorescence quantum yield along with tunable photoluminescence (from blue to orange emission), which make them an ideal candidate for the detection of volatile organic compounds.